Behavioral and toxicological responses of Rhodnius prolixus and Triatoma infestans (Hemiptera: Reduviidae) to 10 monoterpene alcohols - Moretti, Ariadna Noelia (2013)
The effect on locomotor activity, the repellency, and the knock-down produced by 10 monoterpene alcohols were evaluated on first-instar nymphs of Rhodnius prolixus and Triatoma infestans, vectors of Chagas disease. A video tracking technique was used to evaluate locomotor activity and repellency by exposure to papers impregnated with monoterpenes. Eugenol on R. prolixus and (S)-cis-verbenol on T. infestans did not modify the locomotor activity. The remaining monoterpenes produced hyperactivity on both species, although the concentration required was at least a 1,000 times higher than that of deltamethrin (positive control). Carvacrol, eugenol, and geraniol resulted as repellent as N,N-diethyl-m-toluamide (positive control) for both species. A similar result was observed for almost every monoterpene on T. infestans. Knock-down effect was evaluated by exposing the nymphs in closed recipients. The order of increasing toxicity on R. prolixus was (KT50 values in min): geraniol (213.7) < α-terpineol (164.5) < linalool (124.2) < carvacrol (111.6) < eugenol (89.8) < thymol (78.9), and on T. infestans: α-terpineol (289.8) < eugenol (221.3) < carvacrol (164.2) < linalool (154.9) < thymol (96.7). All monoterpenes were less toxic than the positive control, dichlorvos (3.6 min for R. prolixus and 3.9 min for T. infestans). After 7 h of exposure, (-)-carveol, citronellol, and menthol (on both species) and geraniol (on T. infestans) produced <50% of knock-down. After these results, it is worthwhile to explore more deeply the potential of these compounds as tools for controlling Chagas disease vectors.